Experimentation the Influence of Problem-Based Learning Model on Critical Thinking Ability and Understanding the Mathematical Concept of Class VII MTs - Setiawan, Rois Mahfud; Merona, Senja Putri (MEJ (Mathematics Education Journal), 2019)
This study aimed to determine whether the problem based learning models was better than conventional learning models in terms of critical thinking and mathematics conceptual understanding. Based on observations at MTs-N Sampung Ponorogo, it was obtained that students’ mathematics conceptual understanding and critical thinking were quite low. This research was a quasi-experimental with the population students of class VII MTs-N Sampung Ponorogo. The sample was class VII A given a conventional learning model and class VII B given a problem-based learning model. Reasearch data was collected by using test. Pretest and postest was used to get preliminary and final data. Pretest data was analyzed by using t-test while posttest data was analyzed by using the Mann Withney U test. The results of this study were the students’ ability on critical thinking and matematical conceptual understanding used problem based learning models was better than students’ used conventional learning models